Th17 Cells in Depression: Are They Crucial for the Antidepressant Effect of Ketamine? - Cui, Meiying; Dai, Wanlin; Kong, Jing; Chen, Hongzhi (Frontiers in Pharmacology, 2021)
Background: Major depressive disorder is associated with inflammation and immune processes. Depressive symptoms correlate with inflammatory markers and alterations in the immune system including cytokine levels and immune cell function. Th17 cells are a T cell subset which exert pro-inflammatory effects. Th17 cell accumulation and Th17/Treg imbalances have been reported to be critical in the pathophysiology of MDD and depressive-like behaviours in animal models. Th17 cells are thought to interfere with glutamate signalling, dopamine production and other immune processes. Ketamine is a newly characterised antidepressant medication which has proved to be effective in rapidly reducing depressive symptoms. However, the mechanisms behind these antidepressant effects have not been fully elucidated. Method: Literature about Th17 cells and their role in depression, and the antidepressant effect of ketamine are reviewed, with the possible interaction networks discussed. Result: The immune-modulating role of Th17 cells may participate in the antidepressant effect of ketamine. Conclusion: As Th17 cells play multiple roles in depression, it is important to explore the mechanisms of action of ketamine on Th17 cells and Th17/Treg cell balance. This provides new perspectives for strengthening the antidepressant effect of ketamine while reducing its side effects and adverse reactions.